Shared responsibility and civic engagement in very old age - Kruse, Andreas; Schmitt, Eric (Research in human development, 2015)
Although late-life potentials are increasingly recognized as a valuable resource for shaping social change, contributions of the very old to civil society are still regularly overlooked. The authors outline a comprehensive perspective on very old age (or the fourth age), which integrates vulnerability and developmental potential, and report findings from the Generali study of the very old in Germany. This mixed-methods study included 400 qualitative biographical interviews with people aged 85+ and a standardized survey of 800 employees of municipalities and voluntary organizations. The authors found that feelings of shared responsibility and motives for engagement in family and community, especially for younger generations, were highly prevalent among the very old participants. Approximately one half of them reported being civically engaged, mostly in informal settings, and many had been engaged before. The very old participants emphasized the importance of positive intergenerational relationships, physical health, positive perceptions of aging, and supportive environments as major factors that might promote their civic engagement. However, perspectives of institutional staff were different. Institutional staff rated the very old more negatively as compared with the young-old and saw the barriers to civic engagement primarily within the individuals (e.g., in their old age and poor health). The authors' findings indicate that lacking institutional opportunity structures may contribute to the exclusion of some very old people from civic life.
Gesehen am 17.07.2017